Pertumbuhan Laba Dalam Ukuran Rasio Keuangan - Nisa Indri Yani; Ashari Sofyaun; Matyani (Universitas Sains dan Teknologi Komputer, 2025)
The purpose of the study is to determine the position of financial ratios in forming profit growth in chemical sub-sector companies during 2019-2023 listed on the Indonesia Stock Exchange. This research approach uses secondary data types in the form of financial and annual reports. The findings of the partial research results Current Ratio and Total Assets Turnover does not affect profit growth, on the other hand the Debt To Equity Ratio and Net Profit Margin successfully influenced profit growth positively.